ChemInform Abstract: An Unnoticed Inorganic Solid Electrolyte: Dilithium Sodium Phosphate with the Nalipoite Structure. Issue 16 (22nd April 2014) - Lopez, Maria C.; Ortiz, Gregorio F.; Arroyo‐de Dompablo, Elena M.; Tirado, Jose L.
Abstract Orthorhombic Li2NaPO4 is synthesized by stirring aqueous solutions of LiOH, NaOH, and H3PO4 followed by drying at 700 °C in air overnight.